Media representations of the female members of the Portuguese parliament: the “case” of the Parity Parliament - Cabrera, Ana; Martins, Carla; Flores, Teresa Mendes (Brazilian journalism research, 2011)
This article is part of a wider research project entitled “Female politics - gender policies and visibility strategies of female MPs “, whose objective is the study of representations of female members of Parliament in the journalistic and photojournalistic discourse after the Portuguese democratic revolution of April 25, 1974. Here we can draw some conclusions arising from the empirical analysis of the journalistic coverage of the “Parity Parliament”, a pseudo-event which took place from January 31 to February 1, 1994, at the national Parliament, organized with the goal of bringing the problems of gender inequality in the political arena into the media agenda.